SYNTACTICAL ERROR ANALYSIS ON DESCRIPTIVE TEXT: A CASE STUDY ON SENIOR HIGH SCHOOL STUDENTS AT SMK MUHAMMADIYAH UNGARAN - HARDIANY, DEWI ROSNITA; BUDIATI (English Literature Department, Faculty of Economics, Law, and Humanities, 2023)
Mastery of good grammatical structures is very important for language learning especially for writing skill. The present study focuses on the most common syntactic errors in terms of sentence structure made by students of SMK Muhammadiyah Ungaran in writing English descriptive paragraph. This study used a qualitative descriptive approach with analytical methods. The researcher used Dulay's theory to perform error analysis at the level of surface strategy taxonomy. Data collection techniques used observation and measurement, while data collection tools used observation sheets and written tests. From the results of the study it can be concluded that from 147 sentences, there are 75 sentences in the category of syntactic errors at the surface strategy taxonomy level. From types of errors: omission error 28 errors (37.3%), addition error 24 errors (32%), misformation error 14 errors (18.7%), misordering error 9 errors (12%). It is suggested or other researchers to carry out research on the analysis of syntactic errors at different levels, for example on the linguistic category taxonomy aspect or on the comparative taxonomy aspect.